2014
DOI: 10.1007/s11693-014-9138-6
|View full text |Cite
|
Sign up to set email alerts
|

Quantum entanglement in photoactive prebiotic systems

Abstract: This paper contains the review of quantum entanglement investigations in living systems, and in the quantum mechanically modelled photoactive prebiotic kernel systems. We define our modelled self-assembled supramolecular photoactive centres, composed of one or more sensitizer molecules, precursors of fatty acids and a number of water molecules, as a photoactive prebiotic kernel systems. We propose that life first emerged in the form of such minimal photoactive prebiotic kernel systems and later in the process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 58 publications
0
23
0
Order By: Relevance
“…It is becoming clear that components of living systems use quantum principles, for instance, by absorbing light energy and transferring it across a series of molecules–a fundamental quantum process, where quantum entanglement can be viewed as a form of quantum superposition [40]. One of the factors that can influence coherence is the environmental temperature, as this indicates the energy of a particle, and thus its ability to interact with other components.…”
Section: The Quantum Anglementioning
confidence: 99%
See 1 more Smart Citation
“…It is becoming clear that components of living systems use quantum principles, for instance, by absorbing light energy and transferring it across a series of molecules–a fundamental quantum process, where quantum entanglement can be viewed as a form of quantum superposition [40]. One of the factors that can influence coherence is the environmental temperature, as this indicates the energy of a particle, and thus its ability to interact with other components.…”
Section: The Quantum Anglementioning
confidence: 99%
“…Certainly, it seems likely that quantum tunnelling and entanglement were essential for the beginnings of life, especially in relation to photosynthesis, allowing a greater spectrum of photons to be gathered and more efficient transfer of electrons [40,51]. Indeed, many biomolecules may have been selected for their ‘quantum criticality’, and thus behave somewhere between an insulator and a conductor, so also potentially acting as charge carriers [52].…”
Section: The Quantum Anglementioning
confidence: 99%
“…9 11 12 Delivered by Ingenta to: Chinese University of Hong Kong IP: 185. 13 The resulting statement of our above mentioned quantum mechanical investigations is that quantum effects are omnipresent despite the fact that these artificial minimal cells are relatively large and wet, and all molecules are vibrating and rotating. Albert Einstein, Boris Podolsky, and Nathan Rosen described the EPR paradox 17 early in 1935.…”
Section: Introductionmentioning
confidence: 94%
“…The LANL research project on neutral radical molecules (including bioorganic) for quantum information processing [1][2][3][4][5][6][7][8][9][10][11][12][13] has been supported by the USA Department of Energy under Contract No. W-7405-ENG-36.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Erwin Schrödinger in his 1944 book "What is life" predicted some of the basic characteristics of DNA before it had been discovered [14]. More recently, it has been suggested that quantum effects would have been selected for at the beginnings of life due to their ability to improve efficiency -in particular, quantum tunnelling and superposition [29,30]. Indeed, the concept of directed "quantum evolution" has been proposed, which could explain how the first "self-replicator" molecules arose using basic quantum principles and gets around the problem of how, given the enormous degrees of freedom even a relatively short 15-20 unit peptide or nucleic acid displays, could have arisen [31].…”
Section: The Emergence Of Quantum Biologymentioning
confidence: 99%